Asian Banking Crises: A Review of Valuable Lessons from Thailand, Indonesia, and Korea - Roida, Herlina Yoka (Jurnal Widya Manajemen & Akuntansi, 2004)
This paper examines to what extent has Asian countries suffered from the banking crisis. The paper employs a systematic framework to assess the occurrence and magnitude of Asian Banking crisis in some 'tiger countries' of Asia hit by the crisis: Thailand, Indonesia and Korea. The paper will give an overview of the financial crisis for these countries and what factors triggered the crisis. The crisis framework also allows assessing how the crisis has effect to the countries based on the some factors: macro factors, financial factors, and premature liberalization and information asymmetries. The main reason for the Asian Banking crisis was widespread crisis as well as systematic crisis. Countries that have a strong real sector links will be more affect by the crisis. It would be desirable to consider alternative policy instruments that do not place further stress on the banking sector. Finally, operating and regulator environment should be taken to minimize vulnerability of banking system.